Developing a performance framework for measuring comprehensive, community-based primary healthcare for people with HIV. Issue 4 (2nd December 2015) - Johnston, Sharon; Hogel, Matthew; Burchell, Ann N.; Rebick, Gabriel; Antoniou, Tony; McLaren, Meaghan; Loutfy, Mona; Liddy, Clare; Kendall, Claire
Abstract : Objectives: People with human immunodeficiency virus (HIV) are living longer lives and like many other patients, need a health system better adapted for the management of complex chronic conditions. A key element of system transformation is measuring and reporting on system performance indicators relevant to the different stakeholders. Our objective was to produce a performance measurement framework for assessing the quality of comprehensive community-based primary healthcare for people with HIV. Methods: Semi-structured interviews were performed with HIV providers, advocates, and policy-makers to obtain input on a draft performance framework, constructed using existing HIV-specific indicators, as well as the use of performance data in improving care for people with HIV. Results: Stakeholders were overwhelmingly supportive of the framework's comprehensiveness. Many noted the absence of indicators addressing social determinants of health and had mixed opinions on the importance of indicators addressing access to after-hours care and the frequency of routine screening for behavioural risk factors. The draft framework was modified to reflect stakeholder input, triangulated against expert opinion and recently released HIV care guidelines, and finalized at 79 indicators. The resources and infrastructure to collect and use performance data will have to be improved for performance measurement to contribute to improving care for people with HIV. Conclusions: This framework presents a comprehensive though not exhaustive tool to support performance measurement and improvement in the care for people with HIV. However, advances in data collection and use across the system will be needed to support performance measurement driving quality improvement.